Pertanggungjawaban Keuangan Partai Politik yang Bersumber dari Anggaran Pendapatan Belanja Negara dan Anggaran Pendapatan Belanja Daerah - Abadi, Songga Aurora (Universitas Negeri Malang, 2019)
The purpose of this article is to describe the procedures for the financial accountability of political parties obtained from the State Budget (APBN) or the Local Government Budget (APBD) and the substance of the political party accountability report. The study method uses sociological juridical with case studies. Data collection uses interviews and documentation studies. Political parties obtain funds sourced from the APBN or APBD according to the number of votes obtained at the national level (DPR), provincial (Provincial DPRD), and city/regency (City/Regency DPRD). The use of funds following regulations must allocate a minimum of 60% for political education. Political parties must report financial accountability to the government and the public. Supreme Audit Agency (BPK) audit the financial report. The financial report of political parties in the province is transparent. Financial report has been reported to the government and the public by political parties. The report is not yet sufficiently accountable because the use of finance is still not under the party's statutes/by-laws.